2010
DOI: 10.1016/j.stem.2009.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Term Hematopoietic Stem Cells with Extended but Time-Limited Reconstitution Potential

Abstract: Sustained blood cell production depends on divisions by hematopoietic stem cells (HSCs) that yield both differentiating progeny as well as new HSCs via self-renewal. Differentiating progeny remain capable of self-renewal, but only HSCs sustain self-renewal through successive divisions securely enough to maintain clones that persist life-long. Until recently, the first identified next stage consisted of "short-term" reconstituting cells able to sustain clones of differentiating cells for only 4-6 weeks. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 42 publications
10
152
1
2
Order By: Relevance
“…15 As shown in Figure 1A, CD166 and CD150 fractionated LSK48 16 or LT-HSC with a limited, but consistent, repopulating potential. Limiting dilution analysis (LDA) ( Figure 1D) revealed that the frequency of LT-HSC was highest among CD166 Figure 1I) (FMO controls shown in supplemental Figure 1B).…”
Section: Resultsmentioning
confidence: 84%
“…15 As shown in Figure 1A, CD166 and CD150 fractionated LSK48 16 or LT-HSC with a limited, but consistent, repopulating potential. Limiting dilution analysis (LDA) ( Figure 1D) revealed that the frequency of LT-HSC was highest among CD166 Figure 1I) (FMO controls shown in supplemental Figure 1B).…”
Section: Resultsmentioning
confidence: 84%
“…19,20 In these studies, all patients were on long-term, suppressive pharmacotherapy. Because of their relatively short lifespan, 39 we do not believe intermediate progenitors represent a stable viral reservoir. However, intermediate progenitors could potentially be a dynamic reservoir maintained by low-level viremia in the absence of HAART and as such may warrant further study as a novel target for antiviral therapy.…”
Section: Org Frommentioning
confidence: 96%
“…To circumvent this and to further investigate the Ap2a2-quiescence link, we isolated from independent sorts batches of 30-50 cells of the LT-HSC and multipotent intermediate-term HSC (IT-HSC) 28 populations while in quiescence and in cell cycle for Ap2a2 expression. This IT-HSC population, isolated in the CD49b hi rhodamine low LSK fraction and separable from the classic short-term repopulating HSCs, generates multilineage clones that expand through to 8 weeks.…”
Section: Evaluation Of Ap2a2-transduced Hscsmentioning
confidence: 99%